Microbial diversity in bentonite, a potential buffer material for deep geological disposal of radioactive waste. Issue 2 (February 2019) - Liu, Hongyan; Dang, Xuhong; Zhang, Huifang; Dong, Juancong; Zhang, Zhongxin; Wang, Chao; Zhang, Ruifeng; Yuan, Yayi; Ren, Yue; Liu, Wei; Zhuang, Dajie; Yang, Zhongtian; et al.
Abstract: Many countries are considering long-term disposal of nuclear waste in deep geological repositories (DGRs), encapsulated in metal containers, surrounded by a barrier, and emplaced in the host rock. Bentonite is found to be a safe barrier material because of its physical and chemical properties. The bentonite montmorillonite interlayer contains adsorbed organic matter and microorganisms, and therefore biogeochemical activity must be considered. This study focused on investigating the microbial diversity in Chinese bentonite by 16S rRNA analysis via Illumina sequencing to determine how these microorganisms can potentially influence DGR performance. The bentonite sample contained high microbial diversity, dominated by Archaea and abundant other bacteria. The community of Archaea included Nitrososphaera, Thermogymnomonas, and Methanobrevibacter, which are thought to play significant roles in nitrogen cycling, H2 and O2 consumption, CH4 production, and organic matter degradation. These processes can generate excessive pressure and may compromise the safety of DGRs, and therefore the use of bentonite as a barrier material should be carefully considered.